Multielemental Chemical Analysis of Elements in Mandibular Bone and Teeth in the Rat - Němec, I; Smrčka, V; Mihaljevic, M; Mazánek, J; Pokorný, J (Folia biologica, 2018)
The original article was published in Folia Biologica (Praha) Volume 64, No. 3 (2018), 84-96.